The Ecolexicon Forms in Indonesian Language Textbooks: Ecolinguistic Studies at Adiwiyata School - Rida, Anif; Rokhman, Fathur (Universitas Negeri Semarang, 2021)
The use of language in textbooks needs to be studied scientifically. The Adiwiyata’s school textbooks certainly contain a wealth of words or a set of terms that contain information about meanings that describe the environment (ecolexicon). The form of ecolexicons in textbooks in Adiwiyata schools needs to be studied and get our attention as a way of preserving the environment. This study aims to describe and classify the ecolexicon forms in Indonesian language textbooks at Adiwiyata School. The research data is in the form of fragments of text that are suspected of having an ecolexicon. The data are collected using the observation method, literature study, and documentation. Furthermore, the data are analyzed using the match and divide method. The data validity technique used in this study was triangulation with stages: discussion, re-checking, and judgment experts. Based on the results of data analysis, it is found that ecolexicons are in the form of words and phrases with references in biotic and abiotic. The ecolexicon forms are classified based on three components: (1) environmentally based curriculum, (2) participatory-based environmental activities, and (3) management of environmentally friendly supporting facilities. In the phrase ecolexicon, nominal phrases, verbal phrases and adjective phrases are found. The results of this study can be used as an enrichment material for Indonesian language learning which illustrates the richness of language vocabulary to preserve the environment